Psychological Dimensions of Polygamy: Exploring Motivation, Adaptation, and Marital Conflict in Multiple-Partnership Relationships - Salbiah, Siti; Supriatna, Encup; Irfan; Idawati (GoAcademica Research & Publishing, 2025)
Polygamy is a form of plural marriage that generates complex psychological dynamics for all individuals involved. This practice is not only associated with legal and religious dimensions, but also engages deeper psychological aspects, including personal motivations, emotional adaptation processes, gender-based power relations, and intrapersonal as well as interpersonal conflicts within family life. This article aims to analyze the psychological aspects of polygamy by focusing on three main dimensions: (1) individuals’ psychological motivations for engaging in or accepting polygamous marriage, (2) patterns of psychological adaptation that develop within polygamous families, and (3) forms of psychological conflict and their implications for mental health. This study employs a qualitative method through a library research approach and a descriptive-analytical analysis of literature in psychology, family sociology, and gender studies. The findings indicate that polygamy is often associated with high levels of emotional tension, particularly among women and children, and tends to encourage coping mechanisms that are not always adaptive in the long term. This article emphasizes that a psychological perspective is a crucial element in understanding, evaluating, and formulating social and policy responses to polygamous practices in a more comprehensive manner.